The Central and the Peripheral in the Novel “Yaum Raiaa Lilmawt” (A Great Day to Die) by the Algerian Author Samir Kassimi - Lalmi, Ahlam (Journal of Human Sciences, 2023)
The Algerian novel has had a variety of experiences during its growth, many of which have pushed it in new directions, using a variety of viewpoints, several contemporary works have depicted the cohabitation and conflict between the Ego and the Other, the West and the East, and between the Ego and the Ego. The paper poses many queries. Questioning the dichotomy of the center and the periphery, which has carved out a place for itself inside the Algerian cultural and intellectual pattern, this debate now stretches beyond the identification of the Ego and that of the Other and touches on the ideology of the inside. The purpose of this paper is to shed light on the central view of the peripheral characters of various belongings and cultures, as well as on the concept of coexistence and conflict between intellectual and human cultures, which assemble such a dichotomy within one society?